Computer-Aided Design of Microfluidic Very Large Scale Integration (mVLSI) Biochips Design Automation, Testing, and Design-for-Testability - Hu, Kai; Chakrabarty, Krishnendu; Ho, Tsung-Yi (Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of flow-based, microfluidic VLSI. The authors describe and solve in a comprehensive and holistic manner practical challenges such as control synthesis, wash optimization, design for testability, and diagnosis of modern flow-based microfluidic biochips. They introduce practical solutions, based on rigorous optimization and formal models. The technical contributions presented in this book will not only shorten the product development cycle, but also accelerate the adoption and further development of modern flow-based microfluidic biochips, by facilitating the full exploitation of design complexities that are possible with current fabrication techniques. Offers the first practical problem formulation for automated control-layer design in flow-based microfluidic biochips and provides a systematic approach for solving this problem; Introduces a wash-optimization method for cross-contamination removal; Presents a design-for-testability (DfT) technique that can achieve 100% fault coverage at the logic level, i.e., complete defect coverage for all valves and microchannels; Includes a method for fault diagnosis in flow-based microfluidic biochips, which detects leakage and blockage defects in both control and flow layers.